1998
DOI: 10.1046/j.1440-1754.1998.00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of children associated with parental participation during induction of general anaesthesia

Abstract: Parental participation in anaesthetic induction of children can reduce distress at parental separation without any negative consequences. With proper preparation and education, parents should be encouraged to be present during the induction of general anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…Potential benefits from parental presence at induction of anaesthesia include reducing or avoiding the fear and anxiety that might occur in both the child and its parents while being separated as the child is taken to the operating room, reducing the need for preoperative sedatives, and improving the child's compliance during anaesthesia induction. While some reports suggest that parental presence during anaesthesia induction decreases the anxiety of the child and its parents and improves the cooperation of the child (13,14), others showed no effects on the behavioural or psychological measures of paediatric anxiety (15) and no effect on parental anxiety and satisfaction (16). A recent study showed no additive effect of a combination of oral premedication with midazolam and parental presence at induction on the anxiety of children undergoing surgery but did report reduced parental anxiety and increased parental satisfaction (17).…”
mentioning
confidence: 98%
“…Potential benefits from parental presence at induction of anaesthesia include reducing or avoiding the fear and anxiety that might occur in both the child and its parents while being separated as the child is taken to the operating room, reducing the need for preoperative sedatives, and improving the child's compliance during anaesthesia induction. While some reports suggest that parental presence during anaesthesia induction decreases the anxiety of the child and its parents and improves the cooperation of the child (13,14), others showed no effects on the behavioural or psychological measures of paediatric anxiety (15) and no effect on parental anxiety and satisfaction (16). A recent study showed no additive effect of a combination of oral premedication with midazolam and parental presence at induction on the anxiety of children undergoing surgery but did report reduced parental anxiety and increased parental satisfaction (17).…”
mentioning
confidence: 98%
“…However, this practice has long been a matter of dispute [21]. Some authors have reported that allowing the parents to be present decreased the anxiety scores of both the children and their parents [24]. Other authors have claimed that the practice had no effect on anxiety [25].…”
Section: Discussionmentioning
confidence: 99%
“…It was expected that the results of this project would concur with the literature and show a preference towards having a support person present during anesthesia induction. In the pediatric population, family presence has been reported to benefit the patient and the parents 17,18,20,26,28 …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that high levels of social support foster a positive effect on the recovery process, adjustment to physical ailments, and decreased opiate requirements by patients after surgery 14–16 . Many studies have examined the effectiveness of social support during anesthesia induction and other medical procedures in pediatric patient populations 17–21 . Social support in the form of family presence has been reported in emergency departments, neonatal intensive care units, and intensive care units 21–23 .…”
Section: Purpose Of the Projectmentioning
confidence: 99%
See 1 more Smart Citation